A critical role of foxp3a-positive regulatory T cells in maintaining immune homeostasis in zebrafish testis development. (20th September 2020) - Li, Xianmei; Zhang, Fenghua; Wu, Nan; Ye, Ding; Wang, Yaqing; Zhang, Xiaofan; Sun, Yonghua; Zhang, Yong-An
Abstract: Suppressive regulatory T cells (Treg cells) play a vital role in preventing autoimmunity and restraining excessive immune response to both self- and non-self-antigens. Studies on humans and mice show that the Forkhead box p3 (Foxp3) is a key regulatory gene for the development and function of Treg cells. In zebrafish, Treg cells have been identified by using foxp3a as a reliable marker. However, little is known about the function of foxp3a and Treg cells in gonadal development and sex differentiation. Here, we show that foxp3a is essential for maintaining immune homeostasis in zebrafish testis development. We found that foxp3a was specifically expressed in a subset of T cells in zebrafish testis, while knockout of foxp3a led to deficiency of foxp3a -positive Treg cells in the testis. More than 80% of foxp3a –/– mutants developed as subfertile males, and the rest of the mutants developed as fertile females with decreased ovulation. Further study revealed that foxp3a –/– mutants had a delayed juvenile ovary-to-testis transition in definite males and sex reversal in about half of the definite females, which led to a dominance of later male development. Owing to the absence of foxp3a -positive Treg cells in the differentiating testis of foxp3a –/– mutants, abundant T cells and macrophages expand to disrupt an immunosuppressive milieu, resulting in defective development of germ cells and gonadal somatic cells and leading to development of infertile males. Therefore, our study reveals that foxp3a -positive Treg cells play an essential role in the orchestration of gonadal development and sex differentiation in zebrafish.